(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3CHG gQjQI Yf GdfHj Udi Gddg Ydjg hSde bGd (B: (3CMaXg bGd Cf GdfHj Udi Gddg Ydjg hSde cGf jbQC aj UdGI GdUHM jhe GdLeYI Cde JfRjd hgd CJi MOKfG YHO Gddg MOKfj CHj KfG jMji Hf SYjO bGd KfG YHO Gddg Hf SYjO Hf CHj gfO s
(3BNQgG (B:s
(3Yf CHj GdeJhcd GdfGLj , Yf CHj SYjO GdNOQj bGd (B: (3cGf QShd Gddg Udi Gddg Ydjg hSde EPG bGe ef Gddjd hGSJaJM UdGJg hcHQ bGd SHMGfc Gddge hHMeOc , JHGQc GSec , hJYGdiOc , Ke jbhd (B: (3Gddg CcHQ KdGKGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs